Effects of self-regulated strategy development on EFL learners’ reading comprehension and metacognition - Roohani, Ali; Asiabani, Shiva (Penerbit UKM, 2015)
In most academic courses, success in school depends, in large part, on students’ ability to read effectively and implement the reading content to their future learning. Nevertheless, the lack of evidence-based instructional strategies in reading makes reading comprehension in a foreign language more difficult. In this light, learning about reading strategies has become an important issue because it provides the basis for a substantial amount of learning in literacy education and foreign language teaching/learning. This study then examined the effectiveness of a reading comprehension instruction (self-regulated strategy development, SRSD) on Iranian EFL learners’ reading comprehension of argumentative texts, and compared the effectiveness of such an instruction with nonstrategic-based (i.e., traditional) instruction. Additionally, it examined the metacognitive effects of participation in the nonstrategic-based instruction and strategic-based one, drawing on the TWA strategy (i.e., thinking before reading, thinking while reading, and thinking after reading). To achieve of this study aims, 70 Iranian EFL learners from a language school participated in the study with a pre-test and post-test control-group design. To collect data, reading summaries and a metacognitive awareness inventory (MAI) were used. Also, eht Oxford Placement Test was used to ensure the homogeneity of the participants at the entry phase, in terms of the target language (English) level. The analysis of covariance on the data indicated that the strategic-based i.e., SRSD, instruction had a positive impact on the participants’ reading comprehension of argumentative texts in the experimental group (i.e., SRSD group). Also, the effect of SRSD instruction on the participants’ reading comprehension of argumentative texts was significantly greater in the SRSD group than the non-SRSD (control) one. In addition, SRSD instruction significantly improved the L2 participants’ metacognition (including metacognitive awareness and regulation). The results draw L2 teachers’ attention to the importance of teaching self-regulated strategies as a way to improve argumentative reading and metacognition of L2 learners.